Pengaruh Variasi Lama Fermentasi Kombucha Rimpang Jahe Putih dengan Pemanis Stevia Terhadap Kuantitas Kandungan Vitamin C dan Kadar Antioksidan - Izzah Anis Rodhiyah; Ambarwati Ambarwati; Luthfania Marsha Putri (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the effect of fermentation time on the vitamin C content and antioxidant levels in white ginger kombucha sweetened with stevia. This research used experimental methods and a Completely Randomized Design with 1 factor, namely fermentation time of 11 days and 13 days with 3 replications each. Analysis Quantitative data (vitamin C content, antioxidant levels) were analyzed using quantitative descriptive methods. Meanwhile, for qualitative data (pH, physical and biological properties) qualitative descriptive methods are used. The research results showed that the antioxidant content in the 13 day fermentation was 73.21%, while in the 11 day fermentation it was 70.50%. The vitamin C content in white ginger kombucha with stevia sweetener at 13 days of fermentation was 24.18 ml/100g and at 11 days of fermentation was 18.95 ml/100g. In conclusion, the fermentation time affects the vitamin C content and antioxidant levels. The antioxidant levels in white ginger kombucha with stevia sweetener take 13 days of fermentation compared to 11 days of fermentation. Keywords: Antioxidants, Fermentation, White Ginger, Kombucha, Vitamin C